The Review of Act Number 39 year 2004 Concerning The Placement and Protection for Indonesian Workers Abroad - Lalu Husni; Idrus Abdullah; RR Cahyowati (Faculty of Law, University of Mataram, 2017)
Labor migration in the era of free trade is a necessity, as part of the international community, Indonesia must participate in the globalization era, so it can not withstand nationals to seek a better life abroad. The purpose of this study to know and understand the weaknesses of the Act No. 39 of 2004 on the placement and protection of migrant workers, knowing and understanding the formulation of norms of protection of migrant workers to protect it properly. Research methods, normative law research, with the statute approach, conceptual approach, and conceptual approach. The types and sources of legal materials, using primary legal resourse, legal resourse secondary, and tertiary legal resource. Mechanical collection of legal materials, is done by performing a search, collection and documentation, processing and analysis of legal materials through a process of legal reasoning logical, systematic and coherent. Conclusion, weakness No..39 Act of 2004 regarding the Placement and Protection of Migrant Workers so it can not protect properly, this is due to provisions that prohibit or liability, but is not followed by the threat of legal sanction. Their norms do not provide clear who is the subject of law. Their formulation of norms